Infusions and decoctions of mixed herbs used in folk medicine: synergism in antioxidant potential - Guimarães, Rafaela (2011)
Infusions (herbal teas) and decoctions are frequently used to administer oral doses of herbs. Although some herbs are used as single ingredients, they are often prepared as mixtures, as reported by numerous ethnobotanical surveys. The present work was carried out to identify the different types of interaction (synergistic, additive and antagonistic effects) which may be found in the antioxidant activity of preparations from mixtures of the popular herbs Aloysia citrodora (lemon verbena), Foeniculum vulgare (fennel) and Mentha spicata (spearmint). Herbs were prepared using traditional methods, and the effects after different periods of storage, up to 120 days, were also evaluated. Antioxidant activity was evaluated using DPPH radical scavenging activity, reducing power, and inhibition of lipid peroxidation by the β-carotene-linoleate system and the TBARS assay. Known antioxidant compounds such as total phenolics, flavonoids, ascorbic acid and reducing sugars were also determined. Spearmint was found to be present in the herb mixtures with the greatest antioxidant activity and these also had the highest flavonoid content. The most potent antioxidant activity was found in combinations of different herbs, suggesting synergistic effects.